2019
DOI: 10.1002/jmri.26740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravoxel incoherent motion imaging and multiecho dynamic contrast‐based MRI in rectal cancer

Abstract: Background Dynamic contrast‐based MRI and intravoxel incoherent motion imaging (IVIM) MRI are both methods showing promise as diagnostic and prognostic tools in rectal cancer. Both methods aim at measuring perfusion‐related parameters, but the relationship between them is unclear. Purpose To investigate the relationship between perfusion‐ and permeability‐related parameters obtained by IVIM‐MRI, T1‐weighted dynamic contrast‐enhanced (DCE)‐MRI and T2*‐weighted dynamic susceptibility contrast (DSC)‐MRI. Study Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Furthermore, in participants undergoing neoadjuvant treatment, low tumor BF was also associated with shorter OS (Table 4). Low D*, which has been previously shown to be correlated with tumor BF (10), was also associated with shorter PFS (HR = 0.82; 95% confidence interval: 0.70, 0.96; P = .01) ( Table 4, Fig 6c). No other functional MRI parameters were associated with PFS (for example, K trans : HR = 0.01, P = .25; DR 2 *-peak: HR = 0.97, P = .57; f: HR = 0.04, P = .40) or OS (see Table E6 [online] for full list of results).…”
Section: Survivalmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, in participants undergoing neoadjuvant treatment, low tumor BF was also associated with shorter OS (Table 4). Low D*, which has been previously shown to be correlated with tumor BF (10), was also associated with shorter PFS (HR = 0.82; 95% confidence interval: 0.70, 0.96; P = .01) ( Table 4, Fig 6c). No other functional MRI parameters were associated with PFS (for example, K trans : HR = 0.01, P = .25; DR 2 *-peak: HR = 0.97, P = .57; f: HR = 0.04, P = .40) or OS (see Table E6 [online] for full list of results).…”
Section: Survivalmentioning
confidence: 59%
“…Details of the postprocessing have been published previously (10). In brief, acquired multiecho data were used to extract two dynamic time series: T1-and T2*-weighted series.…”
Section: Image Postprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36][37][38] It is interesting to see that the correlation can be observed both in human tumors and animal xenografts; however, some studies have found no significant correlation. Bakke et al 32 found no significant correlation between f and microvessel density or vessel size in 12 rectal cancer patients, and Li et al 38 also found no significant correlation between f and microvessel density in 16 liver tumors in rabbits (r = 0.281, P = 0.291). Conversely, IVIM parameter maps obtained by clustering approaches with Gaussian mixture models might be useful for the identification of tumor subregions with proliferative activity (Ki-67 index).…”
Section: Validation With Histologymentioning
confidence: 99%
“…Subsequently, dynamic enhanced magnetic resonance technology was proposed, and studies suggested that MRIenhanced scanning can improve the accuracy of rectal cancer staging [21]. Bakke et al [22] found that the preoperative staging accuracy of dynamic enhanced MRI was as high as 92%. After NCRT treatment, tumor cells died, the cell morphology changed, and the production inflammatory substances led to cell edema, making it difficult to distinguish the boundary between the lesion and other tissue, so that the accuracy of T staging was reduced.…”
Section: Discussionmentioning
confidence: 99%